Comparative study between continuous and interrupted suturing for rectus sheath closure in exploratory laparotomy - Sayak Roy; Kanchan Kundu; Susavan Das; Kuiri, Shib Shankar (Asian Journal of Medical Sciences, 2022)
Background: Exploratory laparotomy is a major surgical procedure. Midline laparotomy is the most common technique of opening the abdomen as it is simple, provides adequate exposure to all four quadrants, and affords quick exposure with minimal blood loss. Laparotomy wounds have been closed in various ways in terms of continuous versus interrupted closure, single layer versus mass closure, and absorbable versus non-absorbable sutures. Aims and Objectives: The aim of the study was to find out the technique of rectus sheath closure in patients undergoing exploratory laparotomy that can reduce the burden of complications in post-operative period. Materials and Methods: It is a hospital-based prospective randomized observational study which was conducted in a rural-based tertiary care hospital and medical college with a time frame of about 1½ years. A total number of 74 patients of adult age group (21–70 yrs) admitted in general surgery ward of Bankura Sammilani Medical College and Hospital, undergoing exploratory laparotomy. Results: Thirty-seven (50%) patients of midline laparotomy were closed in continuous technique. Rest 37 (50%) patients were closed in interrupted technique. The hospital stay was similar in both groups. There was no significant difference in incidence of wound infection (P=0.4687). Wound dehiscence and requirement of burst abdomen repair was significantly higher in continuous suture group as compared to interrupted suture group, but mean closure time (P<0.0001) and mean suture length (P=0.0436) were significantly higher in interrupted suture group. Conclusion: The major complication of emergency laparotomy is wound dehiscence which leads to increased morbidity and subsequent requirement of re-operation of burst abdomen and hospital cost. In our study, we found that interrupted suturing method of abdominal closure is better in respect to major post-operative complications though it requires more suture length and time.